National Health Examination Survey, Cycle I, 1959-1962: Cardiovascular Findings ([Verlag nicht ermittelbar], 1989)
The National Health Examination Surveys, Cycle I (NHES I), conducted during the period 1959-1962, were designed to secure statistics on the health status of the population of the United States. More specifically, their purpose was to determine the prevalence of certain chronic diseases, the status of dental health, and the distributions of auditory and visual acuity and certain anthropometric measurements. This collection contains information on cardiovascular findings collected from a medical history questionnaire, physician's examination, blood pressure readings, ECG readings, chest x-rays, and a test for serum cholesterol. Data are also supplied on the incidence of headaches, fainting, strokes, chest pain, shortness of breath, heart pain, high blood pressure, and heart trouble.